(Re)Thinking Authoritarianism in Democracy: The Public Denunciation of State Violence During the Pandemic in Argentina 2020–21 - Mira, Julieta (2022)
This chapter examines the expressions of authoritarianism that can occur in non-authoritarian regimes, whereby the most extreme examples are arbitrary killings carried out by public officials. I seek to provoke critical reflections on the need to observe, analyse, and denounce the authoritarianism that persists in democratic countries and which infringes on people´s most fundamental rights, such as the right to life or the right to live free from torture. The goal is to offer a means of accounting both for different forms of authoritarianism and for public response strategies in the form public denunciations.